The COVID-19 pandemic impact on clinical load of plastic and reconstructive surgery in a tertiary care hospital of north India: A retrospective comparative analysis - Mohd Altaf Mir; Debarati Chattopadhyay; Nishank Manohar; Madhubari Vathulya; Vishal Mago; Akshay Kapoor; Neeraj Rao (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The objective of the study was to analyze and determine statistically significant impact of the COVID-19 on clinical load of plastic and reconstructive surgery practices. MATERIALS AND METHODS: The retrospective analysis and comparison of the number of patients visiting to outpatient clinic, number of patients admitted, number of patients operated in the plastic and reconstructive surgery department during the COVID-19 pandemic months of January 2020-June 2020 with the same months of preceding non-COVID-19 year was done. The data obtained were tabulated in Microsoft Excel spread sheet and the statistical analysis done using MedCalc statistical software. RESULTS: The mean ± standard deviation of patients attended in outpatient department (OPD), admitted in inpatient department (IPD), emergency surgeries performed, and elective surgeries performed during -COVID-19 versus COVID-19 pandemic period is (651.167 ± 310.42 vs. 212.5 ± 307.591), (83.5 ± 16.263 vs. 34.333 ± 53.74), (5.167 ± 4.243 vs. 3.333 ± 4.95), and (74.333 ± 28.284 vs. 40.833 ± 60.811), respectively. The difference in means is highly significant statistically in the number of patients attended in OPD, admitted in IPD, and elective surgeries performed during pre-COVID versus COVID period; however, the difference in the means is not statistically significant in the number of emergency surgeries performed during pre-COVID versus COVID period. CONCLUSION: The COVID-19 pandemic has significantly reduced the number of patients attended in OPD, admitted in IPD, and elective surgeries performed in the department of plastic surgery. However, there is a reduction in number of emergency surgeries but statistically insignificant. The strategy is to use telemedicine portal e-Sanjeevani services for OPD, encourage admission of patients with reverse transcription polymerase chain reaction negative for COVID-19, and perform reconstructive and esthetic plastic surgery operative procedures using COVID-19 appropriate precautions.